OLAHAN MAKANAN DAN MINUMAN BERBAHAN DASAR BUAH TAMPOI - Jimmy Situmorang; Vasco A.H. Goeltom; Kevin Gustian Yulius (Journal FAME: Journal Food and Beverage, Product and Services, Accomodation Industry, Entertainment Services, 2022)
Tampoi or Tampui (baccaurea macrocarpa) is a widespread endemic plant known from the area of  Kalimantan, Sumatera, and Malay Peninsula. This fruit is a rare fruit with a sweet and sour taste. The fruit is full of antioxidant which can protect body cells from free radical damage. At present, the use of Tampoi fruit is scarce and people of Kalimantan usually prepare Tampoi fruit as tuak or traditional beverage or just directly eat the fruit. The purpose of this study were: (1) Introduced and elaborate the benefits of the Tampoi fruit. (2) Discovered new flavors created from Tampoi fruit. (3) The author wanted to examine whether Tampoi fruit can be processed into processed foods. (4) Explained the community, especially the people of Kalimantan that Tampoi fruit can be processed into food ingredients and processed foods. (5) Increased the economic price of Tampoi fruit with the aim of preincreasing the economic level of the people of Kalimantan (6) Increased public interest in cultivating Tampoi fruit in order to increase the economic level of the people of Kalimantan. Therefore, to support these goals, product research will be carried out using descriptive, quantitative method by conducting panelist tests so that the resulting products have good standard. Products made from processed Tampoi fruit in this research include cookies, skin chips, fruit chips, noodles, jams, syrup, sorbet and seeds steeping. Based on the results from the research, as many as 8 products which include appetizers, main dishes, desserts, and beverages, were innovated from Tampoi fruit. Keywords:  Tampoi fruit, Kalimantan, Processed Food, Processed Beverages